The Work Life Balance of Teacher (Case Study of Teachers in Jabodetabek) - Dellia Mila Vernia; Syamsul Hadi Senen; Tjutju Kuniarsih; Rofi Rofaida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Teachers have an important role for the education of the Indonesian nation.They must teach during the pandemic corona virus.They have many duties to do. Therefore, it is necessary to improve the quality of teachers in order to achieve the ideals of the Indonesian nation in the intellectual life of the nation. In order for teachers to get maximum work results, it is necessary to achieve job satisfaction that can be felt by teachers in carrying out their activities. In this study using quantitative descriptive methods, namely through questionnaires and interviews were analyzed using PLS which was conducted on 119 teachers in Jakarta. The results of this study found that work stress has an effect on job satisfaction, work life balance has an effect on job satisfaction and work life balance has a relationship with work stress.